2001
DOI: 10.1021/ma001555h
|View full text |Cite
|
Sign up to set email alerts
|

Plasticized Starch/Tunicin Whiskers Nanocomposite Materials. 2. Mechanical Behavior

Abstract: In a previous work [Macromolecules 2000, 33, 8344], nanocomposite materials were obtained using glycerol plasticized starch as the matrix and a colloidal suspension of tunicinan animal cellulosewhiskers as the reinforcing phase. The mechanical behavior of resulting films was characterized in both the linear and the nonlinear range. The effects of the filler and water contents were evaluated, and the results were discussed on the basis of the knowledge of the structural morphology reported in the first part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
304
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(329 citation statements)
references
References 30 publications
23
304
0
2
Order By: Relevance
“…tunicin whiskers. Angles and Dufresne (2001) found that such reinforcement in a starch matrix helped achieve a strong and continuous film. The cited authors proposed that the good film properties, when combining starch with cellulosic nanoreinforcement, could be attributed to hydrogen bonding.…”
Section: Nanocellulose Reinforcement To Overcome Moisture Sensitivitymentioning
confidence: 98%
“…tunicin whiskers. Angles and Dufresne (2001) found that such reinforcement in a starch matrix helped achieve a strong and continuous film. The cited authors proposed that the good film properties, when combining starch with cellulosic nanoreinforcement, could be attributed to hydrogen bonding.…”
Section: Nanocellulose Reinforcement To Overcome Moisture Sensitivitymentioning
confidence: 98%
“…During the last few decades, TPS has received considerable attention among the scientific world (John and Thomas 2008;Belhassen et al 2009;Cañigueral et al 2009;Chaleat et al 2012). As a result, numerous works have been published evaluating their mechanical and thermal properties, water uptake behavior, and/or degradation kinetics in an attempt to adapt these parameters to the technical demands of potential applications (Angles and Dufresne 2001;Carvalho et al 2005;Ayadi et al 2011). In recent years, some companies have started the mass production and commercialization of several starch-based biodegradable polymers.…”
mentioning
confidence: 99%
“…Plasticized starches have been combined wit h v a r i o u s f i b r e s s u c h a s j u t e f i b r e s (Soykeabkaew et al, 2004), ramie fibres (Wollerdorfer & Bader, 1998), flax fibres (Soykeabkaew et al, 2004;Wollerdorfer & Bader, 1998), tunicin whiskers (Angles & Dufresne, 2001), bleached leaf wood fibres (Averous et al, 2001), wood pulp (De Carvalho et al, 2002) and microfibrils from potato pulp (Dufresne et al, 2000). Most of these authors have shown a high compatibility between starch and cellulose-based fibres leading to higher moduli.…”
Section: Biocomposites Based On Plasticized Starchmentioning
confidence: 99%